Sensorimotor Integration in Dyslexic Children under Different Sensory Stimulations - Viana, André R.; Razuk, Milena; de Freitas, Paulo B.; Barela, José A. [UNESP] (Public Library of Science (PLoS), 2013)
Dyslexic children, besides difficulties in mastering literacy, also show poor postural control that might be related to how sensory cues coming from different sensory channels are integrated into proper motor activity. Therefore, the aim of this study was to examine the relationship between sensory information and body sway, with visual and somatosensory information manipulated independent and concurrently, in dyslexic children. Thirty dyslexic and 30 non-dyslexic children were asked to stand as still as possible inside of a moving room either with eyes closed or open and either lightly touching a moveable surface or not for 60 seconds under five experimental conditions: (1) no vision and no touch; (2) moving room; (3) moving bar; (4) moving room and stationary touch; and (5) stationary room and moving bar. Body sway magnitude and the relationship between room/bar movement and body sway were examined. Results showed that dyslexic children swayed more than non-dyslexic children in all sensory condition. Moreover, in those trials with conflicting vision and touch manipulation, dyslexic children swayed less coherent with the stimulus manipulation compared to non-dyslexic children. Finally, dyslexic children showed higher body sway variability and applied higher force while touching the bar compared to non-dyslexic children. Based upon these results, we can suggest that dyslexic children are able to use visual and somatosensory information to control their posture and use the same underlying neural control processes as non-dyslexic children. However, dyslexic children show poorer performance and more variability while relating visual and somatosensory information and motor action even during a task that does not require an active cognitive and motor involvement. Further, in sensory conflict conditions, dyslexic children showed less coherent and more variable body sway. These results suggest that dyslexic children have difficulties in multisensory integration because they may suffer from integrating sensory cues coming from multiple sources. © 2013 Viana et al.
Keywords: association; body equilibrium; body posture; child; clinical article; cognition; controlled study; dyslexia; experimental design; female; human; male; motor performance; school child; sensorimotor integration; sensory stimulation; somatosensory system; standing; stimulus response; task performance; touch; vision; visual information